Breaking Down the Data Path in Digital Health: From Edge to Fog and Beyond - Righi, Rodrigo Da Rosa; Rodrigues, Vinicius Facco; Da Costa, Cristiano Andre; Eskofier, Björn (IEEE Pervasive Computing, 2025)
We live in a disruptive moment where technology plays a crucial role in capturing and analyzing citizens' vital signs in real time. Although having a vast literature on providing health-based intelligent cities, the current articles are disappointing since explanations about scale, module interactions, and processing capabilities need to be detailed. Here, we present an in-depth vision of a new vital sign-driven smart city, highlighting each hierarchical level, its modules, and interactions. This article addresses Internet of Things data capturing, buffering schemes, hierarchical messaging engines, health services, task offloading among layers, person and service priority computation, different dashboards, and notification centers. Although edge, fog, and cloud are not new topics, their scalable blending in favor of delivering digital health is. The presented architecture helps fight against the COVID-19 and other pandemics sequels since data regarding temperature, respiratory rate, heart rate variability, and oxygen saturation of the whole population could be analyzed efficiently.
CRIS-Team Scopus Importer:2025-02-14